2006
DOI: 10.1634/stemcells.2006-0335
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Multipotent Mesenchymal Stromal Cells in Blood

Abstract: Peripheral blood-derived multipotent mesenchymal stromal cells circulate in low number. They share, most although not all, of the surface markers with bone marrow-derived multipotent mesenchymal stromal cells, possess diverse and complicated gene expression characteristics, and are capable of differentiating along and even beyond mesenchymal lineages. Although their origin and physio-pathological function are still unclear, their presence in the adult peripheral blood might relate to some interesting but contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(183 citation statements)
references
References 139 publications
(219 reference statements)
3
171
1
8
Order By: Relevance
“…The concept of MSCs being present in the peripheral blood under normal physiological conditions is divisive; some studies have identified low frequencies of MSCs within the circulation, whereas other studies have been unable to detect their presence (He et al, 2007). However, in response to injury, cytokines, chemokines and neuroendocrine modulators are released, initiating processes thought to mobilise and recruit regenerative cells.…”
Section: Pharmacological Interventions To Enhance Tissue Repairmentioning
confidence: 99%
“…The concept of MSCs being present in the peripheral blood under normal physiological conditions is divisive; some studies have identified low frequencies of MSCs within the circulation, whereas other studies have been unable to detect their presence (He et al, 2007). However, in response to injury, cytokines, chemokines and neuroendocrine modulators are released, initiating processes thought to mobilise and recruit regenerative cells.…”
Section: Pharmacological Interventions To Enhance Tissue Repairmentioning
confidence: 99%
“…With respect to bone repair, this new concept is plausible because there is an abundant reserve of endogenous adult stem cells in bone marrow [21]. These endogenous progenitor cells can be mobilized to the PB [1,11,12,15,17,22,36,48,52].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, they could locally migrate to the sites of inflammation from the surrounding solid tissues (such as WAT), arrive through the systemic circulation, or both [42] . MSC are virtually absent in the peripheral circulation of healthy individuals although hypoxia and inflammation signals are believed to result in MSC mobilization and migration from their niche [94,117,118] . The possibility of spontaneous MSC mobilization in disease has been widely speculated upon, and could underlie their recruitment by tumors although this remains to be tested.…”
Section: Resultsmentioning
confidence: 99%